High-temperature-resistant geopolymer based on wollastonite fibers and preparation method of high-temperature-resistant geopolymer
By introducing wollastonite fibers into the geopolymers, optimizing their pore structure and fiber bridging, the problem of strength loss of building materials in high temperature environments is solved, and the mechanical properties and high temperature resistance of geopolymers are significantly improved.
Patent Information
- Application Number
- CN202411157195.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-22
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing building materials have severe strength losses in high temperature environments, and the ground polymer matrix is brittle and prone to cracking, making it difficult to maintain mechanical properties under high temperature conditions.
Wollastonite fiber is used as a fiber reinforcer to prevent the development of microscopic cracks from becoming macroscopic cracks by optimizing the pore structure and fiber bridging of the geopolymer, thereby improving the mechanical properties and high temperature resistance of the geopolymer.
The compressive strength retention rate of wollastonite fiber geopolymer reaches 72.1% after high temperature of 1000°C, which significantly improves the mechanical properties of the room temperature and reduces the strength loss after high temperature, and provides better high temperature resistance.
Smart Images

Figure CN119191767A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a high-temperature resistant geopolymer based on wollastonite fiber and a preparation method thereof. Background Art
[0002] Concrete is one of the most widely used building materials. However, in the production process of ordinary Portland cement (OPC), a large amount of carbon dioxide is released, accounting for about 8% of the global total. This fact has aggravated the problem of air pollution and smog. Geopolymer is an inorganic polymer with an amorphous three-dimensional network structure formed by solid waste (fly ash, metakaolin, etc.) or natural minerals under high alkaline conditions. The carbon emission of its preparation process is lower than that of Portland cement. Therefore, using geopolymer cement to replace ordinary Portland cement has a significant effect in reducing carbon emissions.
[0003] Fire is one of the main disasters that cause building damage. Existing buildings are mainly constructed with ordinary Portland cement. However, among the hydration products of ordinary Portland cement, the decomposition temperature of ettringite and calcium hydroxide is relatively low, which leads to a large strength loss of the building structure constructed in a high temperature environment. Geopolymers can still show good mechanical properties in high temperature environments. This feature provides new options and possibilities for the research and development and application of high temperature resistant materials.
[0004] Geopolymers also have advantages such as fast hardening, early strength, low permeability, and high durability, but they also have disadvantages such as high brittleness and easy cracking. In order to control the cracking of the geopolymer matrix, improve its brittleness, and improve the mechanical properties, fiber-reinforced geopolymers came into being. The destruction of cement-based / geopolymer-based composite materials is a multi-stage process. First, micro cracks appear under the action of load, and then gradually expand and merge into macro cracks, but the fiber reinforcement effect of macro fibers on micro cracks is not obvious. Therefore, a micro fiber is needed that can bridge the micro cracks of the matrix and prevent micro cracks from developing into macro cracks, thereby possibly improving the mechanical properties of geopolymers.
[0005] The fibers used in the fiber-reinforced cement-based composite materials of the prior art can be roughly divided into the following categories: organic fibers (polypropylene fibers, polyvinyl alcohol fibers, etc.) may produce substances harmful to the human body after high temperatures, inorganic fibers (steel fibers, carbon fibers, etc.) are relatively expensive, and the behavior of nanofibers after high temperatures is unknown. Wollastonite fiber is a kind of microscopic fiber that is not only widely available but also easy to produce. It is widely used in the manufacturing field of high-temperature resistant materials because of its excellent flame retardant and heat-insulating properties. The existing technology mainly focuses on the enhancement of wollastonite fiber on the room-temperature mechanical properties of cement-based / geopolymer-based composites, and lacks relevant research on the effect of wollastonite fiber on the high-temperature resistance of geopolymers. Therefore, in the research and development of fiber-reinforced high-temperature resistant geopolymers, the use of wollastonite fiber has become a novel and effective material choice. Summary of the invention
[0006] Compared with ordinary Portland cement, geopolymers show outstanding low-carbon characteristics and have better high temperature resistance, but high temperature will cause the number of cracks inside the geopolymer to gradually increase and the residual mechanical properties to significantly decrease. In this regard, the purpose of the present invention is to propose a high temperature resistant geopolymer based on wollastonite fiber and a preparation method thereof. The present invention can optimize the pore structure of the geopolymer by incorporating wollastonite fiber, and the bridging effect of the fiber can effectively prevent the development of micro cracks to the macro level, thereby improving the mechanical properties and high temperature resistance of the geopolymer. The wollastonite fiber geopolymer of the present invention has the advantages of good mechanical properties and high temperature resistance.
[0007] To achieve the above object, the present invention is implemented by the following technical solutions:
[0008] The invention provides a high temperature resistant geopolymer based on wollastonite fiber. The high temperature resistant geopolymer comprises the following raw materials in parts by weight: 360-370 parts of metakaolin, 850-855 parts of fly ash, 470-475 parts of alkaline activator, 160-165 parts of water and 121-183 parts of wollastonite fiber.
[0009] As a further optimization scheme of the present invention, the high temperature resistant geopolymer comprises the following raw materials in parts by weight: 365 parts of metakaolin, 852 parts of fly ash, 471 parts of alkaline activator, 162 parts of water, and 121-183 parts of wollastonite fiber.
[0010] As a further optimization scheme of the present invention, the volume content of the wollastonite fiber is 10-15%.
[0011] As a further optimization scheme of the present invention, the volume content of the wollastonite fiber is 10%, and the weight proportion of the wollastonite fiber is 121.7 parts.
[0012] As a further optimization scheme of the present invention, the wollastonite fiber selects any one of two aspect ratio sizes: the first wollastonite fiber has a D50 of 4.21 μm and an aspect ratio of 15-20:1; the second wollastonite fiber has a D50 of 9.2 μm and an aspect ratio of 6-10:1.
[0013] As a further optimization scheme of the present invention, the alkaline activator is prepared by mixing initial potassium water glass and potassium hydroxide in a mass ratio of 473:125.
[0014] As a further optimization scheme of the present invention, the initial modulus of potassium water glass is 2.4, and the modulus of the alkaline activator after preparation is 1.0.
[0015] The present invention also provides a method for preparing a high temperature resistant geopolymer based on wollastonite fiber, the preparation method comprising:
[0016] (1) preparing an alkaline stimulator;
[0017] (2) Weigh fly ash, metakaolin, alkaline activator, water and wollastonite fiber according to the designed mix ratio and set aside;
[0018] (3) Pour the weighed fly ash and metakaolin into a mixer, start the mixer and stir at a low speed until the mixture is evenly mixed; then slowly add the alkaline activator under low-speed stirring, rinse the remaining alkaline activator with the prepared water and add it to the mixer, stir at a low speed until there is no large amount of dry powder, then start medium-speed stirring, stir at a medium speed until there is no dry powder and no large lumps, then start high-speed rotation to obtain a slurry with a certain fluidity;
[0019] (4) After the mixer is adjusted to a low speed, wollastonite fibers are added, and then the high speed mode is turned on to stir until the wollastonite fibers are evenly dispersed, and finally a wollastonite fiber geopolymer slurry is obtained;
[0020] (5) Curing the wollastonite fiber geopolymer slurry to obtain a high temperature resistant geopolymer.
[0021] As a further optimization scheme of the present invention, in step (3), the low-speed stirring speed is 105-110 r / min, the time is 1-2 min, the medium-speed stirring speed is 185-190 r / min, the time is 0.5-1 min, and the high-speed stirring speed is 400-405 r / min, and the time is 1-2 min.
[0022] As a further optimization scheme of the present invention, in step (4), the high-speed stirring speed is 400-405 r / min, and the high-speed stirring time is 2-3 min.
[0023] Compared with the prior art, the technical solution provided by the present invention has the following advantages and beneficial effects:
[0024] (1) The present invention introduces wollastonite fiber into the geopolymer system to prepare a high temperature resistant geopolymer. Wollastonite fiber can bridge the micro cracks of the geopolymer system and prevent the cracks from further developing, thereby ensuring the improvement of its mechanical properties. The geopolymer with wollastonite fiber has a compressive strength of more than 43MPa at room temperature after 28 days, and the compressive strength retention rate after high temperature of 1000°C can reach up to 72.1%, while the compressive strength retention rate of the geopolymer without wollastonite fiber after high temperature of 1000°C is only 10.2%. Compared with the geopolymer without wollastonite fiber, the room temperature mechanical properties are significantly improved and the strength loss after high temperature is reduced.
[0025] (2) The wollastonite fiber material used in the present invention is not only widely available and easy to produce, but also has the advantages of high elastic modulus, good thermal stability, flame retardancy, and heat insulation. After the wollastonite fiber is combined with the geopolymer with high temperature resistance, the advantages of both can be fully utilized to further improve the mechanical properties of the geopolymer at room temperature and high temperature, and can be applied to buildings that require high temperature resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a graph showing the compressive strength results of geopolymers at room temperature and after different high temperatures with the same aspect ratio (15-20:1) and different wollastonite fiber dosages of the present invention.
[0027] Figure 2 This is a graph showing the compressive strength results of geopolymers at room temperature and after different high temperatures at the same dosage (10%) and different aspect ratios of wollastonite fibers according to the present invention. DETAILED DESCRIPTION
[0028] In order to enable those skilled in the art to better understand the technical solution of the present invention, the preferred implementation scheme of the present invention is described below in conjunction with specific embodiments, but it should not be understood as limiting the present invention and is only used as an example.
[0029] The experimental methods or test methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials are obtained from conventional commercial channels or prepared by conventional methods unless otherwise specified.
[0030] Example 1
[0031] In this example, the wollastonite fiber D selected for the geopolymer 50 The particle size is 4.21 μm, the aspect ratio is (15-20:1), the volume dosage is 10%, and the weight portion is 121.7 parts.
[0032] The geopolymer comprises, by weight, 365 parts of metakaolin, 852 parts of fly ash, 471 parts of alkaline activator, 162 parts of additional water and 121.7 parts of wollastonite fiber.
[0033] The preparation method of the geopolymer is as follows:
[0034] (1) An alkaline activator with a modulus of 1.0 (M1.0) is prepared one day in advance, namely, an initial potassium water glass solution with a modulus of 2.4 (M2.4) is mixed with potassium hydroxide.
[0035] (2) Weigh fly ash, kaolin, M1.0 alkaline activator, additional water, and wollastonite fiber according to the designed mix ratio and set aside.
[0036] (3) Pour the weighed fly ash and metakaolin into a mixer, start the mixer and stir at a low speed of 108 r / min for 1-2 min until the mixture is evenly mixed; then slowly add the alkaline activator under low-speed stirring, and then add the prepared water to the alkaline activator to rinse the residual alkaline activator solution and add it to the mixer. Stir at a low speed until there is no large amount of dry powder, then start stirring at a medium speed of 188 r / min for 0.5-1 min. When stirring at a medium speed until there is no dry powder and no large lumps, start rotating at a high speed of 403 r / min for 1-2 min to obtain a slurry with a certain fluidity.
[0037] (4) After the mixer is adjusted to a low speed of 108 r / min, wollastonite fibers are added, and then the high speed mode of 403 r / min is turned on and stirred for 2-3 min until the wollastonite fibers are evenly dispersed, and finally a wollastonite fiber geopolymer slurry is obtained.
[0038] (5) The geopolymer slurry obtained in step (4) is poured into a 40 mm × 40 mm × 40 mm mold for compressive strength testing, and is demoulded within 24 hours after being covered with a film, and is cured (temperature 25 ± 2 ° C, humidity ≥ 95%) until the test age of 28 days.
[0039] The geopolymer samples that reached 28 days old were placed in a high temperature test chamber, and the temperature was raised at a rate of 10°C / min to reach the target temperatures (200°C, 600°C, 1000°C). After the target temperature was kept for 1 hour, the test chamber was closed and the test pieces were allowed to cool naturally before testing their mechanical properties.
[0040] Example 2
[0041] In this example, the wollastonite fiber D selected for the geopolymer 50 The length-to-diameter ratio is 9.2 μm and (6-10:1). The volume dosage is 10% and the weight portion is 121.7 parts.
[0042] The geopolymer comprises, by weight, 365 parts of metakaolin, 852 parts of fly ash, 471 parts of alkaline activator, 162 parts of additional water and 121.7 parts of wollastonite fiber.
[0043] The preparation method of the geopolymer is as follows:
[0044] (1) An alkaline activator with a modulus of 1.0 (M1.0) is prepared one day in advance, namely, an initial potassium water glass solution with a modulus of 2.4 (M2.4) is mixed with potassium hydroxide.
[0045] (2) Weigh fly ash, kaolin, M1.0 alkaline activator, additional water, and wollastonite fiber according to the designed mix ratio and set aside.
[0046] (3) Pour the weighed fly ash and metakaolin into a mixer, start the mixer and stir at a low speed of 108 r / min for 1-2 min until the mixture is evenly mixed; then slowly add the alkaline activator under low-speed stirring, and then add the prepared water to the alkaline activator to rinse the residual alkaline activator solution and add it to the mixer. Stir at a low speed until there is no large amount of dry powder, then start stirring at a medium speed of 188 r / min for 0.5-1 min. When stirring at a medium speed until there is no dry powder and no large lumps, start rotating at a high speed of 403 r / min for 1-2 min to obtain a slurry with a certain fluidity.
[0047] (4) After the mixer is adjusted to a low speed of 108 r / min, wollastonite fibers are added, and then the high speed mode of 403 r / min is turned on and stirred for 2-3 min until the wollastonite fibers are evenly dispersed, and finally a wollastonite fiber geopolymer slurry is obtained.
[0048] (5) The geopolymer slurry obtained in step (4) is poured into a 40 mm × 40 mm × 40 mm mold for compressive strength testing, and is demoulded within 24 hours after being covered with a film, and is cured (temperature 25 ± 2 ° C, humidity ≥ 95%) until the test age of 28 days.
[0049] The geopolymer samples that reached 28 days old were placed in a high temperature test chamber, and the temperature was raised at a rate of 10°C / min to reach the target temperatures (200°C, 600°C, 1000°C). After the target temperature was kept for 1 hour, the test chamber was closed and the test pieces were allowed to cool naturally before testing their mechanical properties.
[0050] Example 3
[0051] In this example, the wollastonite fiber D selected for the geopolymer 50 The length-to-diameter ratio is 4.21 μm (15-20:1), the volume dosage is 15%, and the weight portion is 182.5 parts.
[0052] The geopolymer comprises, by weight, 365 parts of metakaolin, 852 parts of fly ash, 471 parts of alkaline activator, 162 parts of additional water and 182.5 parts of wollastonite fiber.
[0053] The preparation method of the geopolymer is as follows:
[0054] (1) An alkaline activator with a modulus of 1.0 (M1.0) is prepared one day in advance, namely, an initial potassium water glass solution with a modulus of 2.4 (M2.4) is mixed with potassium hydroxide.
[0055] (2) Weigh fly ash, kaolin, M1.0 alkaline activator, additional water, and wollastonite fiber according to the designed mix ratio and set aside.
[0056] (3) Pour the weighed fly ash and metakaolin into a mixer, start the mixer and stir at a low speed of 108 r / min for 1-2 min until the mixture is evenly mixed; then slowly add the alkaline activator under low-speed stirring, and then add the prepared water to the alkaline activator to rinse the residual alkaline activator solution and add it to the mixer. Stir at a low speed until there is no large amount of dry powder, then start stirring at a medium speed of 188 r / min for 0.5-1 min. When stirring at a medium speed until there is no dry powder and no large lumps, start rotating at a high speed of 403 r / min for 1-2 min to obtain a slurry with a certain fluidity.
[0057] (4) After the mixer is adjusted to a low speed of 108 r / min, wollastonite fibers are added, and then the high speed mode of 403 r / min is turned on and stirred for 2-3 min until the wollastonite fibers are evenly dispersed, and finally a wollastonite fiber geopolymer slurry is obtained.
[0058] (5) The geopolymer slurry obtained in step (4) is poured into a 40 mm × 40 mm × 40 mm mold for compressive strength testing, and is demoulded within 24 hours after being covered with a film, and is cured (temperature 25 ± 2 ° C, humidity ≥ 95%) until the test age of 28 days.
[0059] The geopolymer samples that reached 28 days old were placed in a high temperature test chamber, and the temperature was raised at a rate of 10°C / min to reach the target temperatures (200°C, 600°C, 1000°C). After the target temperature was kept for 1 hour, the test chamber was closed and the test pieces were allowed to cool naturally before testing their mechanical properties.
[0060] Comparative Example 1
[0061] In this example, the volume content of wollastonite fiber selected for geopolymer is 0%.
[0062] The geopolymer comprises, by weight, 365 parts of metakaolin, 852 parts of fly ash, 471 parts of alkaline activator and 162 parts of additional water.
[0063] The preparation method of the geopolymer is as follows:
[0064] (1) An alkaline activator with a modulus of 1.0 (M1.0) is prepared one day in advance, namely, an initial potassium water glass solution with a modulus of 2.4 (M2.4) is mixed with potassium hydroxide.
[0065] (2) Weigh fly ash, kaolin, M1.0 alkaline activator and additional water according to the designed mix ratio and set aside.
[0066] (3) Pour the weighed fly ash and metakaolin into a mixer, start the mixer and stir at a low speed of 108 r / min for 1-2 min until the mixture is evenly mixed; then slowly add the alkaline activator under low-speed stirring, and then add the prepared water to the alkaline activator to rinse the residual alkaline activator solution and add it to the mixer. Stir at a low speed until there is no large amount of dry powder, then start stirring at a medium speed of 188 r / min for 0.5-1 min. When stirring at a medium speed until there is no dry powder and no large lumps, start rotating at a high speed of 403 r / min for 3-5 min, and finally obtain a geopolymer slurry without wollastonite fiber.
[0067] (4) The geopolymer slurry obtained in step (3) is poured into a 40 mm × 40 mm × 40 mm mold for compressive strength testing, and is demoulded within 24 hours after being covered with a film, and is cured (temperature 25 ± 2 ° C, humidity ≥ 95%) until the test age of 28 days.
[0068] The geopolymer samples that reached 28 days old were placed in a high temperature test chamber, and the temperature was raised at a rate of 10°C / min to reach the target temperatures (200°C, 600°C, 1000°C). After the target temperature was kept for 1 hour, the test chamber was closed and the test pieces were allowed to cool naturally before testing their mechanical properties.
[0069] Comparative Example 2
[0070] In this example, the wollastonite fiber D selected for the geopolymer 50 The length-to-diameter ratio is 4.21 μm (15-20:1), the volume dosage is 5%, and the weight portion is 60.8 parts.
[0071] The geopolymer comprises, by weight, 365 parts of metakaolin, 852 parts of fly ash, 471 parts of alkaline activator, 162 parts of additional water and 60.8 parts of wollastonite fiber.
[0072] The preparation method of the geopolymer is as follows:
[0073] (1) An alkaline activator with a modulus of 1.0 (M1.0) is prepared one day in advance, namely, an initial potassium water glass solution with a modulus of 2.4 (M2.4) is mixed with potassium hydroxide.
[0074] (2) Weigh fly ash, kaolin, M1.0 alkaline activator, additional water, and wollastonite fiber according to the designed mix ratio and set aside.
[0075] (3) Pour the weighed fly ash and metakaolin into a mixer, start the mixer and stir at a low speed of 108 r / min for 1-2 min until the mixture is evenly mixed; then slowly add the alkaline activator under low-speed stirring, and then add the prepared water to the alkaline activator to rinse the residual alkaline activator solution and add it to the mixer. Stir at a low speed until there is no large amount of dry powder, then start stirring at a medium speed of 188 r / min for 0.5-1 min. When stirring at a medium speed until there is no dry powder and no large lumps, start rotating at a high speed of 403 r / min for 1-2 min to obtain a slurry with a certain fluidity.
[0076] (4) After the mixer is adjusted to a low speed of 108 r / min, wollastonite fibers are added, and then the high speed mode of 403 r / min is turned on and stirred for 2-3 min until the wollastonite fibers are evenly dispersed, and finally a wollastonite fiber geopolymer slurry is obtained.
[0077] (5) The geopolymer slurry obtained in step (4) is poured into a 40 mm × 40 mm × 40 mm mold for compressive strength testing, and is demoulded within 24 hours after being covered with a film, and is cured (temperature 25 ± 2 ° C, humidity ≥ 95%) until the test age of 28 days.
[0078] The geopolymer samples that reached 28 days old were placed in a high temperature test chamber, and the temperature was raised at a rate of 10°C / min to reach the target temperatures (200°C, 600°C, 1000°C). After the target temperature was kept for 1 hour, the test chamber was closed and the test pieces were allowed to cool naturally before testing their mechanical properties.
[0079] Comparative Example 3
[0080] In this example, the wollastonite fiber D selected for the geopolymer 50 The aspect ratio is 2±0.5μm, the volume dosage is 10%, and the weight proportion is 121.7 parts.
[0081] The geopolymer comprises, by weight, 365 parts of metakaolin, 852 parts of fly ash, 471 parts of alkaline activator, 162 parts of additional water and 121.7 parts of wollastonite fiber.
[0082] The preparation method of the geopolymer is as follows:
[0083] (1) An alkaline activator with a modulus of 1.0 (M1.0) is prepared one day in advance, namely, an initial potassium water glass solution with a modulus of 2.4 (M2.4) is mixed with potassium hydroxide.
[0084] (2) Weigh fly ash, kaolin, M1.0 alkaline activator, additional water, and wollastonite fiber according to the designed mix ratio and set aside.
[0085] (3) Pour the weighed fly ash and metakaolin into a mixer, start the mixer and stir at a low speed of 108 r / min for 1-2 min until the mixture is evenly mixed; then slowly add the alkaline activator under low-speed stirring, and then add the prepared water to the alkaline activator to rinse the residual alkaline activator solution and add it to the mixer. Stir at a low speed until there is no large amount of dry powder, then start stirring at a medium speed of 188 r / min for 0.5-1 min. When stirring at a medium speed until there is no dry powder and no large lumps, start rotating at a high speed of 403 r / min for 1-2 min to obtain a slurry with a certain fluidity.
[0086] (4) After the mixer is adjusted to a low speed of 108 r / min, wollastonite fibers are added, and then the high speed mode of 403 r / min is turned on and stirred for 2-3 min until the wollastonite fibers are evenly dispersed, and finally a wollastonite fiber geopolymer slurry is obtained.
[0087] (5) The geopolymer slurry obtained in step (4) is poured into a 40 mm × 40 mm × 40 mm mold for compressive strength testing, and is demoulded within 24 hours after being covered with a film, and is cured (temperature 25 ± 2 ° C, humidity ≥ 95%) until the test age of 28 days.
[0088] The geopolymer samples that reached 28 days old were placed in a high temperature test chamber, and the temperature was raised at a rate of 10°C / min to reach the target temperatures (200°C, 600°C, 1000°C). After the target temperature was kept for 1 hour, the test chamber was closed and the test pieces were allowed to cool naturally before testing their mechanical properties.
[0089] Figure 1 The graph is a result of the compressive strength of geopolymers at room temperature and after different high temperatures under different wollastonite fiber dosages with the same aspect ratio (15-20:1) of the present invention. The wollastonite fiber dosages corresponding to Comparative Examples 1 and 2 and Examples 1 and 3 are 0%, 5%, 10%, and 15%, respectively.
[0090] Figure 2 The compressive strength results of geopolymers at room temperature and after different high temperatures under the same dosage (10%) and different aspect ratios of wollastonite fibers of the present invention are shown in FIG. The aspect ratios of Examples 1, 2 and Comparative Example 3 are (15-20:1), (6-10:1), and (1-3:1), respectively.
[0091] The compressive strengths of the high temperature resistant geopolymers of all the above embodiments and comparative examples at room temperature of 20°C, 200°C, 600°C, and 1000°C after 28 days are shown in Table 1 below.
[0092] Table 1 Compressive strength of geopolymer at different temperatures (unit: MPa)
[0093] 20℃ 200℃ 600℃ 1000℃ Example 1 49.5 61.1 54.6 35.7 Example 2 48.5 60.7 52.2 30.8 Example 3 47.8 57.1 51.9 30.6 Comparative Example 1 38.8 51.2 41.9 3.9 Comparative Example 2 43.6 56.5 46.9 14.9 Comparative Example 3 48.1 59.7 51.3 8.7
[0094] It can be seen from the above Examples 1-3 and Comparative Examples 1 and 2 that the compressive strength of the present invention tends to increase after adding 5%-10% wollastonite fibers, and the compressive strength tends to decrease after adding 15% wollastonite fibers. The room temperature compressive strength and high temperature resistance of the wollastonite fibers with an addition amount of 10% and an aspect ratio of (15-20:1) and (6-10:1) are relatively good, indicating that the high temperature resistance of the geopolymer is the best after adding 10% wollastonite fibers. Among them, the compressive strength retention rates of the wollastonite fibers with an aspect ratio of (15-20:1) at high temperatures of 200°C, 600°C, and 1000°C are 123.5%, 110.4%, and 72.1%, respectively.
[0095] It can be seen from the above-mentioned Examples 1-2 and Comparative Examples 1 and 3 that the aspect ratio of the wollastonite fiber in the present invention has little effect on the compressive strength of the geopolymer after high temperatures of 200°C and 600°C; at a high temperature of 1000°C, as the aspect ratio of the wollastonite fiber increases, the compressive strength of the geopolymer is significantly improved, and the compressive strength retention rate increases from 18.0% to 63.6% and then to 72.1%.
[0096] The above are only preferred embodiments of the present invention. It should be noted that the above preferred embodiments should not be regarded as limiting the present invention, and the protection scope of the present invention should be based on the scope defined by the claims. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the spirit and scope of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A high temperature resistant geopolymer based on wollastonite fiber, characterized in that: The high temperature resistant geopolymer comprises the following raw materials in parts by weight: 360-370 parts of metakaolin, 850-855 parts of fly ash, 470-475 parts of alkaline activator, 160-165 parts of water, and 121-183 parts of wollastonite fiber.
2. The high temperature resistant geopolymer based on wollastonite fiber according to claim 1, characterized in that: The high temperature resistant geopolymer comprises the following raw materials in parts by weight: 365 parts of metakaolin, 852 parts of fly ash, 471 parts of alkaline activator, 162 parts of water, and 121-183 parts of wollastonite fibers.
3. The high temperature resistant geopolymer based on wollastonite fiber according to claim 2, characterized in that: The volume content of the wollastonite fiber is 10-15%.
4. The high temperature resistant geopolymer based on wollastonite fiber according to claim 3, characterized in that: The volume content of the wollastonite fiber is 10%, and the weight portion of the wollastonite fiber is 121.7 parts.
5. The high temperature resistant geopolymer based on wollastonite fiber according to claim 1, characterized in that: The wollastonite fiber is selected from any one of two aspect ratios: the first wollastonite fiber D 50 The second type of wollastonite fiber D 50 It is 9.2μm and the aspect ratio is 6-10:
1.
6. The high temperature resistant geopolymer based on wollastonite fiber according to claim 1, characterized in that: The alkaline activator is prepared by mixing initial potassium water glass and potassium hydroxide in a mass ratio of 473:
125.
7. The high temperature resistant geopolymer based on wollastonite fiber according to claim 6, characterized in that: The initial modulus of potassium water glass is 2.4, and the modulus of the alkaline activator after preparation is 1.
0.
8. A method for preparing a high temperature resistant geopolymer based on wollastonite fiber according to any one of claims 1 to 7, characterized in that: The preparation method comprises: (1) preparing an alkaline stimulator; (2) Weigh fly ash, metakaolin, alkaline activator, water and wollastonite fiber according to the designed mix ratio and set aside; (3) Pour the weighed fly ash and metakaolin into a mixer, start the mixer and stir at a low speed until the mixture is evenly mixed; then slowly add the alkaline activator under low-speed stirring, rinse the remaining alkaline activator with the prepared water and add it to the mixer, stir at a low speed until there is no large amount of dry powder, then start medium-speed stirring, stir at a medium speed until there is no dry powder and no large lumps, then start high-speed rotation to obtain a slurry with a certain fluidity; (4) After the mixer is adjusted to a low speed, wollastonite fibers are added, and then the high speed mode is turned on to stir until the wollastonite fibers are evenly dispersed, and finally a wollastonite fiber geopolymer slurry is obtained; (5) Curing the wollastonite fiber geopolymer slurry to obtain a high temperature resistant geopolymer.
9. The method for preparing a high temperature resistant geopolymer based on wollastonite fiber according to claim 8, characterized in that: In step (3), the low-speed stirring speed is 105-110 r / min, and the time is 1-2 min; the medium-speed stirring speed is 185-190 r / min, and the time is 0.5-1 min; and the high-speed stirring speed is 400-405 r / min, and the time is 1-2 min.
10. The method for preparing a high temperature resistant geopolymer based on wollastonite fiber according to claim 8, characterized in that: In step (4), the low-speed stirring speed is 105-110 r / min, and the time is 1-2 min; the high-speed stirring speed is 400-405 r / min, and the high-speed stirring time is 2-3 min.
Citation Information
Patent Citations
Silica fume-based alkali activator modified high-temperature-resistant geopolymer and preparation method thereof
CN117486544A
Heat and fire resistant geopolymer materials
US20230090940A1
Cited By
Alkali-activated MK-BFS inorganic adhesive as well as preparation method and application thereof
CN120441217A
Alkali-activated mk-bfs inorganic adhesive and preparation method and application thereof
CN120441217B
Composite material and wollastonite fiber modified high-temperature-resistant cementing material as well as preparation method and application thereof
CN121181298A